Motives for public exposure to specialized sports satellite channels and the gratifications achieved from it: A survey study on the public of the city of Baghdad - ali, layla (ALBAHITH ALALAMI, 2022)
Motives for public exposure to specialized sports satellite channels and the gratifications achieved about it - Research presented by (Dr. Dr. Laila Ali Jumaa), Imam Al-Kadhim College (peace be upon him) - Department of Information-2021.       The research aims to know the extent of public exposure to specialized sports satellite channels, and what gratifications are achieved from them, and to reach scientific results that give an accurate description of exposure, motives and gratifications verified by that exposure, and the research objectives are summarized in the following:• Revealing the habits and patterns of public exposure to specialized sports satellite channels?• Identify the reasons for the public's preference for specialized sports satellite channels?• Disclose the motives and gratifications achieved by the public from exposure to specialized sports satellite channels?The researcher used the survey method to collect data by designing a questionnaire, as a tool to reveal the motives and gratifications achieved among the public from exposure to specialized sports satellite channels. areal), and it was paired with the non-probability (purpose) sample from the audience groups that watch specialized sports satellite channels, as it achieves the research objectives, and the research reached several results that can be summarized as follows:• The results of the research showed that the majority of the respondents watched the specialized sports satellite channels, on a continuous basis, “always” with a number of repetitions amounting to (120%), respondents and at a rate of (60%).• The results of the research showed that the respondents prefer watching specialized sports satellite channels in the second evening period from (6 pm - 10 pm), and the number of respondents was (127), with a percentage of (63.5%).• There is a statistically significant correlation between the public's exposure to specialized sports satellite channels and the related motives of this exposure, and the degree of need or motivation for exposure to specialized sports satellite channels is at a high level.• There is a statistically significant correlation between the public's motives for exposure to specialized sports satellite channels and the resulting gratifications from this exposure. The result indicates that the degree of saturation achieved from exposure to specialized sports satellite channels was at a high level.